Salmonella infection of breast implant associated with traveler's diarrhea: A case report. (December 2018) - Hall, Bradley R.; Billue, Katherine L.; Sanders, Stacey E.; Meyer, Bria R.; Johnson, Perry J.
Abstract: We present the first case of traveler's diarrhea resulting in breast implant infection. An otherwise healthy 34-year-old female underwent breast augmentation. Five months later, while vacationing in Cancun, Mexico, she developed abdominal pain and diarrhea that progressed to include fevers and chills. Her symptoms persisted until she returned to the United States, at which point her primary care physician evaluated her on the fourth day of her illness. An abdominal CT scan was unremarkable; however, a complete metabolic panel demonstrated elevated transaminases. Her symptoms soon resolved without treatment. Fourteen days after symptom resolution, the patient developed right breast pain. She was evaluated in the surgical clinic where the breast was tender to palpation, swollen and without erythema. An ultrasound demonstrated a small amount of homogenous fluid surrounding the implant. She was prescribed amoxicillin–clavulanate 875–125 mg BID; however, she presented three days later with worsening pain, swelling and new erythema. She was taken to the operating room, where the abscess was incised, drained and the implant removed. Cultures grew Salmonella serogroup C. Patients should be counseled regarding the potential for hematogenous seeding of the breast cavity and implant following severe illness and bacteremia. It may be reasonable to provide patients with breast implants who are traveling to areas at high-risk for traveler's diarrhea or areas with limited medical resources with an antibiotic to take if moderate to severe symptoms of traveler's diarrhea were to develop while away.